The first crocodyliform from the Chubut Group (Chubut Province, Argentina) and its phylogenetic position within basal Mesoeucrocodylia - Leardi, Juan Martín (2009)
A new crocodyliform specimen is presented here found in the Cerro Castaño Member of the Cerro Barcino Formation (Chubut Group). The material consists of cranial and postcranial remains that represent a new taxon that has strong affinities with Peirosauridae, but also shares derived features present in Araripesuchus. The phylogenetic relationships of this new taxon were tested through a cladistic analysis depicting it as a member of the Peirosauridae. The inclusion of Barcinosuchus within this clade of basal mesoeucrocodylians is supported by the presence of hypapophyses up to the third or fourth dorsal vertebrae, anterolateral facing edge on postorbital, quadrate dorsal surface divided in two planes by a ridge; mandibular symphysis tapering anterirorly in ventral view, lateral surface of dentary convex anterior to mandibular fenestra, distal body of quadrate well developed, anteroposteriorly thin and lateromedially broad. The new specimen broadens the temporal and geographical distribution of Peirosauridae during the Cretaceous of Gondwana, representing the southern-most and the most ancient record of the group in Patagonia. The new material also provides insights on the postcranial anatomy of peirosaurids, a group that has been so far studied almost exclusively from cranial material. © 2009 Elsevier Ltd. All rights reserved.